2019
DOI: 10.2217/epi-2018-0087
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed Coding and Noncoding RNAs in CoCl 2 -Induced Cytotoxicity of C2C12 Cells

Abstract: Aim: We aimed to explore potential regulators of coding and noncoding RNAs (ncRNAs) in Co(II) ion-induced myo cytotoxicity. Materials & methods: We confirmed the toxic effects of Co(II) on mouse skeletal C2C12 myotubes by CoCl2, and performed the expression profiles of circular RNAs (circRNAs), long noncoding RNAs (lncRNAs) and mRNAs using microarray analysis. We constructed co-expression, competing endogenous RNA and cis/trans regulation networks for ncRNAs, and filtered 71 candidate circRNAs with coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Except starvation and fasting, multiple physiological and pathological conditions, including immobilization, mechanical unloading, cancer and chronic disease, can also trigger muscle atrophy (3,4). Our previous studies demonstrated that decreases in actin fiber size resulted in reduced expression of myogenin, and elevated expression of atrogin-1 induced by cobalt dichloride mimicking hypoxia, which subsequently led to skeletal muscle atrophy (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Except starvation and fasting, multiple physiological and pathological conditions, including immobilization, mechanical unloading, cancer and chronic disease, can also trigger muscle atrophy (3,4). Our previous studies demonstrated that decreases in actin fiber size resulted in reduced expression of myogenin, and elevated expression of atrogin-1 induced by cobalt dichloride mimicking hypoxia, which subsequently led to skeletal muscle atrophy (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…102 circFGFR4 binding to miR-107 promotes cell differentiation by targeting Wnt3a in bovine primary myoblasts. 95 Our research group has identified the coding potentials and known functional domains of 75 circRNAs during mouse C2C12 myoblast differentiation, 30 as well as 71 circRNAs with coding potential and known functional domains during pathological conditions of Co (II) ion-induced myocytotoxicity in mouse skeletal 108 In the future, other circRNAs encoding proteins involved in muscle development may be discovered. 104 Moreover, circSNX29 sponges miR-744 to facilitate bovine myoblasts differentiation and inhibit cell proliferation by activating the Wnt5a/Ca 2+ signalling pathway.…”
Section: Muscle Developmentmentioning
confidence: 99%
“…107 In addition to promoting proliferation, circ-ZNF609 is translated into a protein, but the function of the flagged protein is unknown in human myoblasts. 95 Our research group has identified the coding potentials and known functional domains of 75 circRNAs during mouse C2C12 myoblast differentiation, 30 as well as 71 circRNAs with coding potential and known functional domains during pathological conditions of Co (II) ion-induced myocytotoxicity in mouse skeletal 108 In the future, other circRNAs encoding proteins involved in muscle development may be discovered.…”
Section: Muscle Developmentmentioning
confidence: 99%
“…A systematic review of our groups provided a summary of the known functions and mechanisms of lncRNAs in skeletal muscle development ( Chen et al, 2020 ). However, 4,409 lncRNAs are differentially regulated by CoCl 2 ( Chen et al, 2019 ), which triggers atrophy in skeletal C2C12 myotubes ( Chen et al, 2017 ), indicating the potential involvement of lncRNAs in muscle wasting.…”
Section: Introductionmentioning
confidence: 99%